2017
DOI: 10.4172/2329-9096.1000422
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Reliability and Validity of a Newly Developed Intimate Partner Violence Screening Tool for use in Physical Therapy Practice

Abstract: We conducted a study to investigate the reliability and validity of a newly developed Intimate Partner Violence (IPV) Screening Tool. The literature shows that victims of intimate partner violence identify health-care practitioners as potential sources of support. Meanwhile health care professionals are often unprepared to identify and help victims appropriately. Our survey addressed psychosocial, socio-economic and physical constructs influencing prevalence and screening accuracy for IPV. Four experts in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Most included articles discussed opportunities for rehabilitation interventions for survivors of IPV (68%, n = 30). Eight articles (18%) described or evaluated rehabilitation interventions ( Cerny et al, 2019 ; de Oliveira & Ferigato, 2019 ; Fitzgerald et al, 2017 ; Gutman et al, 2004 ; Helfrich & Rivera, 2006 ; Jones et al, 2021 ; Mangum et al, 2019 ; Walton et al, 2017 ), and seven articles (16%) explored rehabilitation professionals’ knowledge of or attitudes toward IPV ( Clark et al, 1996 ; de Oliveira & Ferigato, 2019 ; Johnston et al, 2001 ; Macpherson et al, 2022 ; Shahgangar, 2004 ; Sivagurunathan et al, 2019 ; Williamson et al, 2004 ). One article touched on both rehabilitation interventions and knowledge and attitudes and is included in both categories ( de Oliveira & Ferigato, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most included articles discussed opportunities for rehabilitation interventions for survivors of IPV (68%, n = 30). Eight articles (18%) described or evaluated rehabilitation interventions ( Cerny et al, 2019 ; de Oliveira & Ferigato, 2019 ; Fitzgerald et al, 2017 ; Gutman et al, 2004 ; Helfrich & Rivera, 2006 ; Jones et al, 2021 ; Mangum et al, 2019 ; Walton et al, 2017 ), and seven articles (16%) explored rehabilitation professionals’ knowledge of or attitudes toward IPV ( Clark et al, 1996 ; de Oliveira & Ferigato, 2019 ; Johnston et al, 2001 ; Macpherson et al, 2022 ; Shahgangar, 2004 ; Sivagurunathan et al, 2019 ; Williamson et al, 2004 ). One article touched on both rehabilitation interventions and knowledge and attitudes and is included in both categories ( de Oliveira & Ferigato, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…One was a broader qualitative exploration of the ways OTs assist survivors of domestic violence within primary care groups, noting the breadth of settings where OTs might support survivors (e.g., community workshops, home visits) and the variety of interventions OTs are equipped to provide (e.g., supporting self-expression related to violence, supporting social participation; de Oliveira & Ferigato, 2019 ). The final article described the evaluation of an IPV screening assessment for use in a PT clinic, noting strong inter-rater reliability and good construct validity for the tool ( Walton et al, 2017 ). A full summary of rehabilitation intervention articles is shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This screening tool exhibited excellent construct and content validity, internal consistency, and inter-rater reliability. 23 A systematic review reported that HITS was one of the most studied screening tools with sensitivity range of 30–100% and specificity range of 86–99%. Sensitivity ranges varied depending on the population.…”
Section: Introductionmentioning
confidence: 99%